Generasi Milineal, Entrepreneurship dan Globalisasi Ekonomi - Shofiyah Shofiyah (Al-Musthofa: Journal of Sharia Economics, 2019)
The era of globalization has greatly impacted the lives of the world community, especially in the economic field. Society is stimulated by various offers in themarket so that everyone is competing to fulfill their consumptive and hedonic desires. This era is very demanding to increase the ability of the community, especially the younger generation in maximizing their potential to be able to compete in the international world so that it is not eroded by the negative influence of the globalization era. Based on these problems, entrepreneurship becomes very important for millennial generations to answer global challenges so that they can lead to the country's goal, namely social welfare.